2002
DOI: 10.1103/physrevb.66.205408
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon polaritons on narrow-ridged short-pitch metal gratings

Abstract: The reflectivity of short pitch metal gratings consisting of a series of narrow Gaussian ridges in the classical mount has been modeled as a function of frequency and in-plane wave vector ͑the plane of incidence containing the grating vector͒ for various ridge heights. Surface plasmon polaritons ͑SPP's͒ are found to be excited even in the zero-order region of the spectrum. These may result in strong absorption of radiation polarized with its electric field in the plane of incidence ͑transverse magnetic͒. For z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
4
28
0
Order By: Relevance
“…These resonances are similar to the resonances found previously on thin Gaussian ridges [7,8]. The instantaneous fields also show that the coupling across the wires is asymmetric, that is, H z goes through a zero inside the metal.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These resonances are similar to the resonances found previously on thin Gaussian ridges [7,8]. The instantaneous fields also show that the coupling across the wires is asymmetric, that is, H z goes through a zero inside the metal.…”
Section: Resultssupporting
confidence: 71%
“…However, it has been shown that surface plasmons may be excited in the zero-order region of the spectrum, as they evolve to form cavity modes in the grooves of the structure [4][5][6]. Further work has also examined the nature of these cavity modes on gratings whose ridges are sufficiently narrow that the surface plasmon modes on each vertical surface may also interact through the metal ridges, as well as across the grooves [7,8]. These cavity modes are essentially the same as the TEM cavity mode in a single groove, except that their evolution from normal surface plasmon modes, due to the periodicity of the structure, means that there are some subtle differences in their dispersion curves from the well-known TEM mode.…”
Section: Introductionmentioning
confidence: 99%
“…These resonances are all the result of diffractive coupling via the periodicity of the array and, therefore, demonstrate strong dispersive character close to the onset of diffraction. Indeed, the band structure is analogous in many ways to the flat-banded TEM waveguide modes observed on deep and narrow grating grooves [16]; however, unlike the TE modes supported by the tubes in the present study, TEM modes have no lower frequency cutoff. Nevertheless, they demonstrate similar dispersion characteristics, anticrossing with the light lines.…”
supporting
confidence: 68%
“…In this region, the band structure can no longer be accurately determined from positions of transmission peaks, because not only do their characters become mixed, but also the shape of the resonant peaks becomes distorted by the dominance of the diffraction feature. We indicate the expected band structure in this region with a broken gray line [16]. It is clear that the higher frequency mode morphs into an N 1 resonance as it moves into the diffracting region (fields not shown), while the lower mode follows the diffracted light line as it decreases in frequency.…”
mentioning
confidence: 78%
“…The method has since been improved and applied to study a wide range of diffractive grating systems [33][34][35][36][37][38][39][40][41]. The essence of the method is to map the periodically structured surface onto a flat plane by the use of a nonorthogonal curvilinear coordinate transformation.…”
Section: Ag Coated Gratingsmentioning
confidence: 99%